Leveraging Organizational Culture to Enhance Employees’ Innovative Performance: Empirical Evidence from the Directorate General of State Assets in Indonesia Mediated by Job Satisfaction - Setyawantika, Mokhamad Arif; Hamidah; Fauzi, Achmad (Journal of Cultural Analysis and Social Change, 2025)
This study examines the influence of organizational culture (OC) on the innovative performance (IP) of public-sector employees, with job satisfaction (JS) serving as a mediating variable, specifically within the Directorate General of State Assets in Indonesia. The research aims to analyze how organizational culture shapes innovative performance and to assess the extent to which job satisfaction strengthens this relationship. Using a quantitative approach with a descriptive survey, data were collected from 361 employees through questionnaires measuring OC, JS, and IP, and analyzed using SMARTPLS4 for model and hypothesis testing. The findings reveal that job satisfaction successfully mediates the relationship between organizational culture and innovative performance, indicating that a positive organizational culture enhances innovation primarily through increased job satisfaction, while the direct effect of culture on innovation is not significant. These results highlight the unique contribution of the study, namely the crucial mediating role of job satisfaction in driving innovation through organizational culture. The study recommends that organizations strengthen positive cultural practices to improve job satisfaction and, consequently, employee innovation. Future research is encouraged to expand the analysis to other government institutions to provide a broader understanding of how culture influences public-sector innovation.